Chromosome aberrations, micronucleus frequency, and catalase concentration in a population chronically exposed to high levels of radon - Ramadhani, Dwi; Purnami, Sofiati; Tetriana, Devita; Sugoro, Irawan; Suvifan, Viria Agesti; Rahadjeng, Nastiti; Wanandi, Septelia Inawati; Wibowo, Heri; Kashiwakura, Ikuo; Miura, Tomisato; Syaifudin, Mukh (International journal of radiation biology, 2023)
To deepen our knowledge on the effects of high levels of indoor radon exposure, we assessed the frequencies of unstable and stable chromosome aberrations and micronucleus (MN), as well as the concentration of an endogenous antioxidant (catalase, CAT), in blood samples of individuals chronically exposed to high indoor radon concentrations in Indonesia (Tande-Tande sub-village, Mamuju, West Sulawesi). Moreover, we also investigated the occurrence of a radio-adaptive response (RAR) in Tande-Tande sub-village inhabitants using the G 2 MN assay. The frequencies of dicentric (DC), acentric (AF), ring (R), and translocation (Tr) chromosomes in Tande-Tande inhabitants were compared to those in people living in a reference area with low levels of indoor radon levels (Topoyo village, Indonesia). The number of MN per 1000 binucleated cells (BNC) and CAT concentration per total protein was quantified and compared between groups. Lastly, we irradiated (2 Gy) phytohemagglutinin-stimulated samples in vitro and measured the frequency of MN to verify the occurrence of a RAR in Tande-Tande sub-village inhabitants. The frequencies of DC, AF, and Tr did not differ between Tande-Tande inhabitants and control subjects (p = 0.350, 0.521, 0.597). The frequency of MN in Tande-Tande inhabitants was significantly lower than that in the control group (p = 0.006). Similarly, CAT concentration in Tande-Tande inhabitants was also significantly lower than that in the control population (p < 0.001). Significant negative correlations were identified for MN number and CAT concentration versus indoor radon concentration, annual effective dose, or cumulative dose both within groups and when all data were analyzed together. Our findings indicate that, despite the high indoor radon levels, Tande-Tande inhabitants are not under oxidative stress, since this group had lower CAT concentration and MN frequency than those in the control group. The negative correlation between MN frequency and indoor radon concentration, annual effective dose, and cumulative dose suggests the occurrence of an RAR phenomenon in Tande-Tande sub-village inhabitants. This interpretation is also supported by the results of the G 2 MN assay, which revealed lower MN frequencies after in vitro irradiation of samples from Tande-Tande sub-village inhabitants than those in samples from the control group (p = 0.0069, for cumulative MN frequency; p = 0.0146, for radiation-induced MN only).